PENGARUH PROFITABILITAS TERHADAP RETURN SAHAM (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2018) - Ririn Ismira Afiyani Kamarullah; Muhsin N Bailusy; Hartaty Hadady (Jurnal Manajemen Sinergi, 2020)
Objective: This study aims to determine the effect of ROA, ROE, EPSand NPM variables on stock returns (Y) partially and simultaneously.The research sample is 45 companies. The data collection techniqueis done by the documentation method, which is collecting data in theform of book literature, journals, and the company's annual financialstatements. The data needed in this study is secondary data from thefinancial statements of manufacturing companies listed on theIndonesia Stock Exchange in the 2014-2018 period. The financialstatements were downloaded from the site www.idx.co.id.Methodology: The analytical method used in this study is the Paneldata regression method as analysis technique used is quantitative.Finding: ROA (H1), ROE (H2), EPS (H3) are accepted (positiveaffect), while H4 (NPM) are accepted (positive affect) at the 5%confidence level.Conclusion:The results showed that ROA has a positive and significant effect onstock returns, the more effective the users of the company's assets,then by itself efforts to increase profits can be maximally generatedand ultimately can increase the value of stock returns. ROE has apositive and significant effect on stock returns, the more effective thecompany is in managing its own capital, then the effort to increasestock returns can be realized. EPS has a positive and significanteffect on stock returns, earnings per share contains importantinformation to make predictions about dividends per share in thefuture. While NPM has a negative and significant effect on StockReturn, the high and low NPMs do not guarantee investors will buythese shares because NPM only makes a profit from each sale